(untitled) (LACCEI, 2024)
We analyze how gender differences, and the social context of the students might affect their learning process in a first physics course, for engineering students in an Ecuadorian university. Starting from previously collected data we statistically established the interdependence of these variables, showing that female and lower income tiers perform at the same level of effectiveness in passing the general physics course. Selecting a sample of 76 students, we applied an inventory concept pre- and post-test to determine to which extent their gender and socioeconomic background affect their academic performance. The pre-test results show that, on average, independently from their socioeconomic background, several misconceptions in basic kinematics and dynamics concepts are spotted. Although the post-test result shows a ten-point improvement, only 40% of the population reaches the minimum passing grade in the individual assessments. Thus, although female and low-income underrepresented tiers, the need for developing more course activities that could strengthen the individual student’s performance is a necessary change in our region.